New and little known species of ptyctimous mites (Acari, Oribatida) from Cameroon - Niedbała, Wojciech; Starý, Josef (Zootaxa, 2014)
Altogether 24 species of ptyctimous mites were found in sifting litter samples from the Cameroon. Twelve new species of the ptyctimous mites, Indotritia montkoupensis sp. nov., Acrotritia furca sp. nov., Acrotritia quasidivida sp. nov., Hoplophthiracarus kumboensis sp. nov., Hoplophthiracarus reticulatus sp. nov., Hoplophthiracarus spinus sp. nov., Steganacarus (Rhacaplacarus) quaternarius sp. nov., Austrophthiracarus bicarinatus sp. nov., Protophthiracarus diatropos sp. nov., Protophthiracarus korupensis sp. nov., Protophthiracarus preptos sp. nov., Atropacarus (Hoplophorella) gibbus sp. nov., from the Cameroon are described and figured. Seven species are recorded for the first time for the Cameroon oribatid mite fauna. A comparison of morphological similarities with the most closely related species is presented. Taxonomical notes and additional information for two ptyctimous species: Acrotritia ardua (C.L.Koch, 1841), Arphthicarus sculptilis (Niedbała, 1988), were added. Keys for Afrotropical species of genera Hoplophthiracarus and Protophthiracarus are presented.